Analysis of the role of motivating operations in the therapeutic verbal interaction - Estal-Muñoz, Víctor; Andrés-López, Natalia; Pereira, Gladis L.; Gálvez-Delgado, Elena; Froxán-Parga, María Xesús (Anales de Psicología / Annals of Psychology, 2023)
The concept of motivating operation (MO) helps to overcome both theoretical and practical problems of the traditional notion of motivation in the study of the therapeutic process. In this research, the role of three types of therapists’ verbalizations with an MO function was analyzed, in addition to their association with clients’ verbal behavior. For this purpose, recordings of 40 clinical sessions belonging to 9 different cases were observed. The ACOVEO System was the observational category system used to identify the therapists’ verbal MOs coded as MO with clinical information, MO with consequences, and MO with pairings. The SISC-CVC was the one used to identify clients’ verbalizations coded as Agreement and Disagreement. Sequential analyses were performed to test the relation between the three different types of MOs with themselves, as well as with clients’ concurrence. Results showed that the different MOs were emitted in chunks and when MO with clinical information was uttered either with MO with consequences or MO with pairings there was a greater association with Agreement (r = 2.47; r = 1.86) rather than with Disagreement (r = -.53; r = -.36). These findings highlight the importance of the emission of MOs that associate directly events with an eliciting component with clients’ behavior, giving more efficacious strategies to the therapists